2020
DOI: 10.1021/acs.jafc.0c01410
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Hordein-Null Barley Lines Reveals Storage Protein Synthesis and Compensation Mechanisms

Abstract: Hordeins are the major barley seed storage proteins and are elicitors of celiac disease. Attempts to reduce the hordein level in barley have been made; however, the resultant pleiotropic effects are less understood. Here, data-independent acquisition mass spectrometry was used to measure proteome-wide abundance differences between wild-type and single hordein-null barley lines. Using comparative quantitative proteomics, we detected proteome-wide changes (∼59%) as a result of the specific reduction in hordein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 50 publications
5
20
0
Order By: Relevance
“…To determine the magnitude of proteome perturbation, the mutant lines were compared with the WT ( Supplementary Figure 1 ). The proteins with perturbed abundance in the BC-mutant line was highly concordant with the changes observed in the parent B- and C-hordein mutant lines ( Bose et al, 2020 ). Additionally, the lys3 mutant, i.e.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…To determine the magnitude of proteome perturbation, the mutant lines were compared with the WT ( Supplementary Figure 1 ). The proteins with perturbed abundance in the BC-mutant line was highly concordant with the changes observed in the parent B- and C-hordein mutant lines ( Bose et al, 2020 ). Additionally, the lys3 mutant, i.e.…”
Section: Resultssupporting
confidence: 72%
“…A heatmap was generated from the differentially abundant proteins identified from pairwise comparisons between WT and DM lines to visualise the link between single and DM lines. The SM proteome abundance profiles were also included in the heatmap to allow contrast to the parent lines ( Figure 4 ) ( Bose et al, 2020 ). Hierarchical clustering shows the grouping of the biological replicates and that the D-hordein mutant line is closely linked to the WT, as D-hordein proportionately represents just 1–2% of total hordein content resulting in a minimal perturbation to the proteome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implementing SWATH-MS, this study highlights one of the main applications of this advanced method in proteome-level alterations studies for investigating modified crops. 149 …”
Section: Proteins In Barley Malt and Beermentioning
confidence: 99%
“…The advancement of mass spectrometry-based proteomics has enabled the routine measurements of thousands of proteins in terms of their abundance, localisation, interactions, and modifications while connecting the large-scale data to gene expression regulation and function [ 89 , 90 ]. Targeted and untargeted proteomics experiments have been widely used to investigate crop responses to the abiotic stress [ 89 , 90 , 91 , 92 ]. Proteomics studies have shown that plant-derived smoke water solutions can improve the abiotic stress tolerance capacity in soybean [ 3 ], chickpea [ 93 ] and rice [ 36 ].…”
Section: Application Of Proteomics To Understand Smoke Water-assismentioning
confidence: 99%